El masoquismo: paradigma de la perversión, el paso de la teoría Freudiana a la teoría Lacaniana sobre la estructura perversa (2019)
The paradigm of perversion is postulated from two theoretical currents; therefore the following thesis will investigate and explain the passage from one theory to another. Being the first theory taught by Freud, who through his text "Three Essays On Sexual Theory" addresses sexual aberrations to conceptualize and classify each of the perverse sexual practices (according to the sexual object and sexual goal), achieving with this writing to conclude that all sexuality is perverse, however it is not until 1927 in his section on fetishism where he establishes renegation as a defense mechanism of perversion, thus differentiating perversion from neurosis. Thus, through renegation he establishes fetishism as a paradigm of perversion because this sexual practice fulfills the function of denying the existence of castration